The Impact of Salt Business on the Socio-Economic Condition of Borimasunggu Village Labakkang District Pangkep Regency - St Nuradryani; Hasriyanti Hasriyanti; Rosmini Maru (UNM Geographic Journal, 2020)
This study aims to determine whether the salt business can affect the socio-economic conditions of salt farmers in Borimasunggu Village, Labakkang District, Pangkep Regency. The independent variable in this study is the salt business, while the dependent variable is the socio-economic condition. The population in this research is the people of Borimasunggu Village who work as salt farmers, while the sample is 22 people. The research method used is a survey method with a quantitative type. The sampling technique was simple random sampling. The instrument used was a questionnaire with a Guttman scale and the data analysis method used the product moment correlation test and simple regression analysis. The results showed that: (1) The significance value was 0.000. Therefore 0.000 <0.05, while for the pearson correlation value, 696 is a positive value with a strong relationship. (2) The coefficient of determination (R2) 0.484 indicates that the socioeconomic conditions of 48.4% are influenced by salt business. So it can be concluded that: (1) there is an effect of salt business on the socio-economic conditions of the residents of Borimasunggu Village, Labakkang District, Pangkep Regency, (2) the magnitude of the influence of business on socio-economic conditions is 48.4% and 51.2% is influenced by other factors.